Effects of the Different Methacrylate Monomers on Bond Strength Between Soft Liner and Acrylic Resin - Bolayir, Giray; Soygun, Koray; Simsek, Selcuk; Yilmaz, Ersen; Dogan, Arife; Boztug, Ali; Murat Dogan, Orhan (Asian Journal of Chemistry, 2013)
In the present study, tensile bond strength between on acrylic resin and a soft liner, molloplast B, was studied. To enhance the bonding capacity between these materials, acrylic resin surface was modified using ethyl methacrylate, iso-butyl methacrylate or tert-butyl methacrylate monomers. The monomers were applied onto the surfaces of methacrylate components for 60, 120 or 180 s and the bond strength values were obtained. The values were statistically compared. Changes on the modified surfaces were investigated by fourier transform infared spectroscopy with attenuated total reflectance (FTIR-ATR). The highest bond strength value was obtained from 120 s treatments with ethyl methacrylate and the lowest value was obtained from 60 s treatments with iso-butyl methacrylate. These high alkyl monomers also had secondary interactions on the acrylic surfaces, evidenced by FTIR-ATR.